Planos de textos narrativos em contos populares: perspectivas para o ensino da escrita no 6° ano do Ensino Fundamental - Alauk, Débora Matos (2022)
This study is part of the research line “Reading, writing and teaching of Portuguese Language”, of the Postgraduate Program in Portuguese Language at the Pontifical Catholic University of São Paulo, and its theme is to understand the narrative text plan as well as the narrative textual sequences of popular tales which can support the teaching of narrative text writing, specifically, in the 6th year of Elementary School. The hypothesis is that the understanding of the short story genre, with regard to the text plan and the narrative textual sequence, contributes to the teaching of writing narrative texts in the 6th year of Elementary School. The research questions are: a) How are text plans and narrative text sequences organized in the folktale genre? and b) What are the perspectives for the teaching of narrative writing provided by the study of the narrative text plan of this genre, taking into account the official documents that guide the teaching of Portuguese Language? The general objective is to understand the text plan and the narrative textual sequences of the folktale genre as elements for the teaching of writing in the 6th year of Elementary School. As for the specific objectives, there are: a) to identify, describe and analyze the text plans and narrative textual sequences that compose texts of the folktale genre; b) reflect on how text plans and narrative textual sequences, considered in the composition of popular tales, can constitute strategies for teaching writing in the 6th year of Elementary School. The theoretical apparatus that supports this study is composed of studies on text plan (ADAM, 2011; CABRAL, 2013; MARQUESI; ELIAS; CABRAL, 2017; MARQUESI et al., 2019; MARQUESI; CABRAL, 2017), textual sequences, in particular, the narrative textual sequences (ADAM, 2011; 2019), narrative and its structure (ADAM; REVAZ, 1997), type elements - tipelementos - (TRAVAGLIA, 2007; 2018), logical organization of the narrative and its components (CHARAUDEAU, 2016) and concept and nature of the narrative (GENETTE, 2013 [1971]; 1979), in addition to those that approach the short story genre (GOTLIB, 2006; GANCHO, 2006; TERRA; PACHECO, 2017), wonderful, fairy, enchantment and popular tales (PROPP, 2001; 2002; AZEVEDO, 2007; ALCOFORADO, 1986), and popular tales and their characteristics (LEAL, 1985; CÂMARA CASCUDO, 2006; GUIMARÃES, 2011). In relation to official education documents, it is based on the National Curriculum Parameters for the Portuguese Language (1998), the National Common Curricular Base (BRASIL, 2018), the City Curriculum − Elementary School − Curricular Component: Portuguese Language (SÃO PAULO, 2019) and the Curriculum of the State of São Paulo: languages, codes and their technologies (SÃO PAULO, 2011). The corpus is composed of four short stories from the book “Tales of cheating the death”, by Ricardo Azevedo: “The man who saw the death”, “The last day in the life of the blacksmith”, “The boy who did not want to die” and “The almost death of Zé Malandro”. The results obtained confirm the hypothesis that the study of the text plan and the narrative textual sequence the way of organizing narratives, especially the principle of intentionality, as well as the narrative processes related to the characters' roles constitutes an important subsidy for the teaching of narrative writing in the 6th year of Elementary School